Impact of Nonlinearity of Climate Damage Functions on Long-term Macroeconomic Projections under Conditions of Global Warming - Kovalevsky, Dmitry V.; Kuzmina, Svetlana I.; Bobylev, Leonid P. (Discontinuity, Nonlinearity, and Complexity, 2026)
A weakly nonlinear climate damage function used by Nordhaus in his DICE model and a strongly nonlinear climate damage function recently proposed by Weitzman are incorporated in the Kellie-Smith—Cox Integrated Assessment model of coupled climate—conomic dynamics, the initial version of which contained only linear climate damages. Long-term projections of the dynamics of coupled climate—economic system are computed with the modified versions of the model. Simulation results for Weitzman function demonstrate pronounced nonlinear emergent dynamics and suggest extremely dramatic long-term economic scenarios for high values of background economic growth rates.